Importance of decentralization for the further development of sports in Ukraine - Tеtіana Dorofieieva; Vladimir Prikhodko (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to substantiate the need to spread the practice of decentralization of power in the field of sports in Ukraine, which will contribute to its further development. Material and methods: generalization of literature and materials from the Internet, abstraction, idealization, analysis and synthesis, induction and deduction. Results: the content of legislative acts of Ukraine on sports development was analyzed, which allowed to establish significant gaps in their content (declarativeness) and to determine the need for qualitative improvement of regional management of sports development. The problem of low efficiency of the state management of sports development in Ukraine needs further elaboration, as it is characterized by extremely weak implementation of the laws of Ukraine, current regulations and departmental acts. Conclusions: the analysis shows that the adopted laws and regulations are not those that largely contribute to the development of sports in the field. This is due to the fact that a significant part of their content is marked by declarativeness and lack of established indicators. Decentralization of power creates stronger organizational and financial preconditions for the reform of physical culture and sports according to the «European model». And this, given the high level of public administration (when the leadership is interested in promoting development, ie qualitative change), can ensure the development of sports. This model of competent management allows you to combine resources and opportunities, including the funds of the state body of sports management, other ministries and agencies involved in physical culture and sports, as well as local authorities and public organizations (national sports federations, existing federations in regions and cities, sports clubs, etc.).